An Exploration of the Construction of Ideological and Political Education Models in College English Courses: A Study on the “BOPPPS + Blended” Teaching Model - Chunying (Pacific International Journal, 2024)
In the context of comprehensive ideological and political education, this study addresses the unique characteristics and practical challenges associated with ideological and political education in college English programs. It employs the “BOPPPS + Blended” teaching model to facilitate this educational endeavor. The construction of the “BOPPPS + Blended” teaching model for ideological and political education in college English courses is delineated into three distinct phases: pre-class online preparation, in-class offline interaction, and post-class online summarization. Additionally, it comprises six structured teaching steps. A comprehensive evaluation approach is implemented that includes student self-reflection, group assessments, and teacher feedback. This model offers several advantages such as clarifying the instructional process, enhancing interactive engagement during lessons, and promoting effective assessment practices aimed at continuous improvement. Moving forward, further research and practical application are essential to refine and expand upon this teaching model to contribute towards cultivating high-quality talents equipped with a global perspective, national sentiment, and social responsibility.